AN ANALYSIS OF CATEGORY-SHIFTS ON THE COMIC TRANSLATION FROM ENGLISH INTO INDONESIAN IN VISUAL TRANSLATION SUBJECT OF ENGLISH DEPARTMENT TIDAR UNIVERSITY - Anik Sholekhah (Faculty of Education and Teachers Training, 2019)
AbstractTranslation comes as the bridge of communication of the people in the world. In the process of translation, the equivalence meaning between source language and target language is very important. Therefore, in the translation of comic from English into Indonesian, the translator used a translation shift to get the equivalence meaning. The objectives of this research are to describe the occurrence of category shift on the comic translation translated by the third semester students in Visual Translation subject of English Department Tidar University and to describe the influences of category shift on transferring meaning from source language into target language. This research applies descriptive qualitative research which is explaining the occurrence of category shift on the comic translation translated by the third semester students of English Department, Tidar University. The data was collected by documentation. The data were analyzed using Catford’s theory (1965) of category shift. The finding of the analysis shows that there are four category shifts occur on the comic translation from English into Indonesian. They are structure shift, class shift, unit shift and intra-system-shift. The influence of category shift on the comic translation causes complete meaning increased meaning, decreased meaning, lost meaning and different meaning. The researcher concluded that the dominant of category shift is structure shift and the influence of shift causes the meaning in the TL is complete meaning.